Social Work Students Acquiring Tools to Help Families Manage their Household Finances - Ahuva Even-Zohar (Journal of Financial Therapy, 2020)
The study examined the impact of a workshop for social work (BSW) students (n=134) aimed at teaching them to assess clients' financial situation and assist them in managing their household finances. Students' attitudes toward the role of social workers in providing material support and helping low-income families to manage their finances were found to be positive both before and after the workshop. Participation in the workshop increased their financial literacy and introduced them to tools that can assist them in helping families living in poverty to rehabilitate their financial situation. The students reported using these tools to a certain extent in their fieldwork training. It is recommended that financial literacy be part of the social work curriculum, and that students be encouraged to use the financial tools they acquire during their fieldwork training.
Keywords: social work students; poverty; financial literacy